(untitled) (Journal of the College of Basic Education, 2023)
The study of childhood and caring for it is one of the most important criteria by which the progress and development of society is measured, as caring for it is an interest in the future of the nation and preparing children and raising them is preparing to meet the challenges posed by the inevitability of development (Al-Fiqhi, 1986: 7)And one of the manifestations of this interest was the development of research methods, as the scientists’ activity tended towards studying the aspects of integrated growth in each age stage and what distinguishes it from the characteristics (Al-Assaf and Abu Latifah, 123: 2009)The main purpose upon which scientists built their opinion about the necessity of caring for children during this particular age stage is the presence of what is known as the critical period. (Abu Jado, 2000) believes that during this period the development of psychological processes accelerates and is highly sensitive and vulnerable to environmental stimuli. Operations during this period, and if their excitement is not appropriate, may lose the ability to acquire the experiences that they should acquire, or the speed of their acquisition may slow down in subsequent periods of growth (Abu Jado, 2000: 68).Piaget supports the theory of the critical period that the early years have a role in activating the child’s intellectual perceptions (Mardan, 2004: 90).Therefore, the child in the pre-school stage needs every possible opportunity to consolidate the basic skills that he has previously acquired and to develop and apply new things (Jones, 1998: 7).Hence, children in early childhood need a purposeful educational institutional system that is commensurate with their developmental characteristics and needs and develops their readiness for future learning. Mental, spiritual and aesthetic (Al-Assaf and Abu Latifa, 2009: 52).